TANGGUNG GUGAT PEJABAT PEMBUAT AKTA TANAH (PPAT) ATAS KELALAIAN MENINDAKLANJUTI SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) MENJADI AKTA PEMBERIAN HAK TANGGUNGAN (APHT) - INTAN SURIANI (PREMISE LAW JURNAL, 2016)
SKMHT is effective when a debtor cannot come over as a requirement for the following-up of making APHT. Basically, SKMHT is given in a certain period of time when PPAT neglects to follow-up SKMHT to become APHT, so that the Bank as the creditor will not financially lucrative. The debtor is asked to reassign SKMHT when the time is due. The result of the research shows that SKMHT is not collateral; it is only an initial effort of a debtor to convince the Bank that he has good faith concerning the credit contract by giving the authority to the Bank to increase the position of the land used for the mortgage to APHT. By the negligence of PPAT in following-up SKMHT to become APHT, PPAT has fulfilled all elements in Article 1365 of the Civil Code. Keywords: Accountability, SKMHT, APHT